Effect of Non-Steroidal Anti-Inflammatory Drugs (NSAID) on Embryogenesis: Animal Model Study - Niklas R. Klein, Lena M. Friedrich, Mia K. Bengeir, Camila M. Fredrik, Thea N. Payne, Damian W. Blake (Academic Journal of Clinicians, 2025)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are important group of pharmacological agents which can be used both as decongestants and as analgesics. It is known that all NSAIDs have a similar mechanism of action, regardless of their chemical structure. They block the synthesis of arachidonic acid derivatives by inhibiting cyclooxygenase. One of the most important criteria in selecting drugs is their safety when taken by pregnant women. However, despite the fact that most NSAIDs are approved for use during all or most of pregnancy, serious studies of their possible teratogenicity are conducted only for acetylsalicylic acid and indomethacin. Information on the effects of other NSAIDs on the embryo and fetus re extremely scarce. Taking into account the fact that acetylsalicylic acid has been shown to have teratogenic and embryotoxic effects on animals, it could be assumed that other NSAIDs, can also have these effects. Over the last 15 years, evidence has accumulated indicating the need for a more thorough, repeated study of this drug, especially its possible effect on the body of the fetus and mother. The aim of this study was to determine the effect of the nonsteroidal anti-inflammatory drugs on the embryogenesis of two genetically distant strains of laboratory mice with regard to the course of pregnancy in female mice, as well as on pre- and post-implantation mortality of embryos, their general development (weight and craniocaudal size) and the frequency of external deformities. It was found that the drug has the ability to delay the overall development of fetuses of all studied lines, especially when used in the last period of pregnancy."